Development of hospital disaster resilience: conceptual framework and potential measurement. Issue 11 (12th September 2013) - Zhong, Shuang; Clark, Michele; Hou, Xiang-Yu; Zang, Yu-Li; Fitzgerald, Gerard
Abstract : Objective: Despite 'hospital resilience' gaining prominence in recent years, it remains poorly defined. This article aims to define hospital resilience, build a preliminary conceptual framework and highlight possible approaches to measurement. Methods: Searches were conducted of the commonly used health databases to identify relevant literature and reports. Search terms included 'resilience and framework or model' or 'evaluation or assess or measure and hospital and disaster or emergency or mass casualty and resilience or capacity or preparedness or response or safety'. Articles were retrieved that focussed on disaster resilience frameworks and the evaluation of various hospital capacities. Result: A total of 1480 potentially eligible publications were retrieved initially but the final analysis was conducted on 47 articles, which appeared to contribute to the study objectives. Four disaster resilience frameworks and 11 evaluation instruments of hospital disaster capacity were included. Discussion and conclusion: Hospital resilience is a comprehensive concept derived from existing disaster resilience frameworks. It has four key domains: hospital safety; disaster preparedness and resources; continuity of essential medical services; recovery and adaptation. These domains were categorised according to four criteria, namely, robustness, redundancy, resourcefulness and rapidity. A conceptual understanding of hospital resilience is essential for an intellectual basis for an integrated approach to system development. This article (1) defines hospital resilience; (2) constructs conceptual framework (including key domains); (3) proposes comprehensive measures for possible inclusion in an evaluation instrument; and (4) develops a matrix of critical issues to enhance hospital resilience to cope with future disasters.